ANALISIS KONTRUKTIVISME ISI PESAN DALAM ANIMASI MENGENAL WAYANG SASAK DARI PERSPEKTIF PENGKARYA - Banyu Lazuardi, Ashar; Anjas Kharisma Nata, I Gede; Kusuma Di Biagi, I Wayan (Berajah Journal, 2024)
Animation media is a form of transferring Sasak wayang media from traditional media to a new form of media or presentation. This research focuses on a two-dimensional (2D) animation work entitled Getting to Know Wayang Sasak. This research aims to determine the content of the message conveyed by the creator in the animated work with the target audience being children aged six to twelve years, or those in elementary school. The method used in this research is descriptive qualitative method. Research data collection techniques are through observation and literature study. The results of the research show that the Getting to Know Wayang Sasak animation is a media animation that contains information about Sasak wayang figures or characters. The constructivism of the message content carried out by the creator is in line with the one-way communication model. The animated characters are also the result of the creator's idea which refers to the original Sasak wayang characters or puppets, and the content of the message in this animation is adapted to the target audience, namely children aged six to twelve years, or those who are still in elementary school.